2014
DOI: 10.1002/bmc.3357
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of erlotinib and its isomeric major metabolites in human plasma using isocratic liquid chromatography–tandem mass spectrometry and its clinical application

Abstract: This study developed a method for the simultaneous determination of erlotinib and its isomeric major metabolites, OSI-413 and OSI-420, in human plasma using an isocratic liquid chromatography-tandem mass spectrometry. Plasma specimens deproteinized with acetonitrile were separated using a 3-µm particle size octadecylsilyl column. The m/z values of the precursor and product ions for the analytes were as follows: erlotinib, 394.2/278.2; and OSI-413 and OSI-420, 380.2/278.2. The total run time was 21 min and no p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 10 publications
0
18
1
Order By: Relevance
“…3. Using this method, the achieved LLOQ values of both drugs were lower than those of previously reported LC-MS/MS methods for ERL [18][19][20][21][22] and TAM [26,[29][30][31][32][33][34][35][36]. These low values of LLOQ allowed the successful application of this method in the trace analysis of the two drugs in clinical studies.…”
Section: Lower Limit Of Detection (Llod) and Of Quantification (Lloq)contrasting
confidence: 58%
See 2 more Smart Citations
“…3. Using this method, the achieved LLOQ values of both drugs were lower than those of previously reported LC-MS/MS methods for ERL [18][19][20][21][22] and TAM [26,[29][30][31][32][33][34][35][36]. These low values of LLOQ allowed the successful application of this method in the trace analysis of the two drugs in clinical studies.…”
Section: Lower Limit Of Detection (Llod) and Of Quantification (Lloq)contrasting
confidence: 58%
“…With the exception of ERL which was previously determined by our research team in rat plasma samples, in combinations with gefitinib, dexamethasone, prednisolone, and ondansetron [23], the current method provided the lowest LLOQ (0.2 ng/mL) described so far for the analysis of TAM. Compared with previously published methods for the determination of ERL [18][19][20][21][22] or TAM [26,[29][30][31][32][33][34][35][36], this method was of a remarkable sensitivity. This is extremely important for trace analysis of the studied drugs and for accurate determination of terminal phase elimination during PK studies.…”
Section: Comparison Between the Proposed Methods Over Previously Repormentioning
confidence: 92%
See 1 more Smart Citation
“…1 (C)), OSI-420 and erlotinib with retention times of 1.1 and 2.2 min, respectively, could be separated from other peaks. Previous studies demonstrated that OSI-413 (desmethyl erlotinib), an isomeric metabolite of OSI-420, was observed between the retention times of OSI-420 and erlotinib in reversed-phase HPLC [16,17]. In those studies, the peak area of OSI-413 was larger than that of OSI-420.…”
Section: Clinical Pharmacokineticsmentioning
confidence: 96%
“…Several analytical methods have been developed using liquid chromatography-tandem mass spectrometry (LC/MS/MS) [11][12][13][14][15][16][17] or high-performance liquid chromatography with ultraviolet detection (HPLC-UV) [3,18,19] to determine the concentrations of erlotinib and/or OSI-420 in human biological samples. LC/MS/MS methods are highly selective and sensitive, but due to their cost and complexity, they are not available in most hospital laboratories.…”
Section: Introductionmentioning
confidence: 99%